PENERAPAN TEKNIK PERNAPASAN BUTEYKO UNTUK MENGATASI POLA NAPAS TIDAK EFEKTIF PADA PASIEN ASMA BRONKHIAL DI RUANG KENANGA RUMAH SAKIT TK II DUSTIRA - Sapitri, Tia; Octaviani, Oky; Malisa, Novi (Jurnal Kesehatan An-Nuur, 2025)
Bronchial asthma is a chronic respiratory disease caused by narrowing of the airway due to a hypersensitivity reaction in the bronchi, causing symptoms in the form of wheezing, coughing, and shortness of breath. Buteyko's breathing technique is a non-pharmacological method that focuses on conscious breath control, with the principle of reducing the frequency and volume of breathing through the practice of holding the breath and breathing slowly controlled through the nose.  The method of this case study is a descriptive method, aiming to describe nursing care in bronchial asthma patients. The subject of this case study used 2 patients as the subject material of the case study, with a nursing diagnosis of ineffective breathing patterns due to bronchial asthma. The focus of the intervention was to provide the application of buteyko breathing techniques for 10 minutes within 3 days with a frequency of 2 times daily. The results showed that both patients experienced improvement in respiratory condition after the 3rd day of application. In patient 1, the respiratory frequency decreased from 28x/min to 20x/min and oxygen saturation increased from 95% to 98%, the use of the respiratory and respiratory muscles of the nasal lobes also decreased significantly. Meanwhile, patient 2  showed a decrease in breathing frequency from 30x/min to 20x/minute, an increase in oxygen saturation from 94% to 97%, but the diffusion occurred more slowly than patient 1. Limitations in the application of buteyko breathing techniques include differences in response speed between patients and the need for repeated education so that patients understand the application correctly. Buteyko breathing techniques are recommended as an effective nonpharmacological intervention in the management of ineffective breathing patterns in bronchial asthma patients, both in hospital and independently at home with consistent training for optimal outcomes.